Effect of Hybridization on Tensile, Shear and Compressive Properties of Carbon Based Fiber Reinforced Composites - Abdurohman, Kosim; Adhitya, Mohammad (Indonesian Journal of Aerospace, 2021)
The high specific stiffness and strength of composites make them widely usedÂ Â in defence, marine, and aerospace applications. Hybrid composites have increased use in high-tech applications. The glass/carbon and KC/carbon hybrid composites manufactured by vacuum assisted resin infusion methods are used in this study. The matrix used for both composites are vinylester resin. The glass/carbon and KC/carbon hybrid laminates arrangement is [G/C/G2/C/G2/C]s and [(KC)2/C3]s, respectively. The mechanical properties are evaluated according to ASTM standards. Fracture micrograph analysis are investigated using SEM. The comparison of mechanical properties and surface fracture of both hybrid composites have been investigated. The tensile and compressive strength of KC/carbon are higher than glass/carbon hybrid composites. However, the shear strength of KC/carbon is lower than glass/carbon hybrid composites. SEM micrograph exhibits that the KC/carbon has a good fiber/matrix and interlayer bond better than glass/carbon hybrid composites.